Impact of the COVID-19 pandemic on the measles elimination status in Armenia - Naira Melkonyan; Mary Ter-Stepanyan; Arman Badalyan; Hasmik Hovhannisyan (Journal of Infection in Developing Countries)
Introduction: The coronavirus disease 2019 (COVID-19) pandemic led to a decrease in immunization rates and measles surveillance, resulting in re-establishment of endemic measles transmission in many countries where measles was previously eliminated.